1998
DOI: 10.1046/j.1461-0248.1998.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress increases the prevalence and intensity of blood parasite infection in the common lizard Lacerta vivipara

Abstract: Parasites affect the life‐histories and fitness of their hosts. It has been demonstrated that the ability of the immune system to cope with parasites partly depends on environmental conditions. In particular, stressful conditions have an immunosuppressive effect and may affect disease resistance. The relationship between environmental stress and parasitism was investigated using a blood parasite of the common lizard Lacerta vivipara. In laboratory cages, density and additional stressors had a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 46 publications
(78 reference statements)
4
77
0
5
Order By: Relevance
“…Conversely, the Romanovs exhibited a serious dulling of the senses and lack of reaction once anaemization was achieved; this necessitated support treatments with rehydrating solutions to allow them to overcome their state of anergy . These results strongly support the hypothesis that, beyond the environmental factors such as stress, nutrition and other conditions, which in general facilitate infections (Agyemang et al, 1990;Bennison et al, 1998;Oppliger et al, 1998) and which are supposed to be particularly relevant in the case of non-native breeds, genetic predisposition plays a major role also in the pathogenesis of TBD.…”
Section: Contrastssupporting
confidence: 84%
“…Conversely, the Romanovs exhibited a serious dulling of the senses and lack of reaction once anaemization was achieved; this necessitated support treatments with rehydrating solutions to allow them to overcome their state of anergy . These results strongly support the hypothesis that, beyond the environmental factors such as stress, nutrition and other conditions, which in general facilitate infections (Agyemang et al, 1990;Bennison et al, 1998;Oppliger et al, 1998) and which are supposed to be particularly relevant in the case of non-native breeds, genetic predisposition plays a major role also in the pathogenesis of TBD.…”
Section: Contrastssupporting
confidence: 84%
“…Parallel glucocorticoid and infection parameters have been measured in few studies; however, these studies have included species ranging from the seahorse (Anderson et al 2011) to amphibians (Kindermann et al 2012;Gabor et al 2013), birds (Lindström et al 2005;Kitaysky et al 2010), lizards (Oppliger et al 1998) and non-human primates Clough et al 2010), indicating the potential of this method to be used in different taxa. This approach has been applied in a small number of stress and disease studies conducted on endangered species in challenging field conditions (Aguirre et al 1995;Chapman et al 2006).…”
Section: Approaches To Understand the Relationship Between Stress Andmentioning
confidence: 99%
“…The bi-directional relationship between stress and infection poses a challenge to establishing causality in observation studies. Experimental approaches can be used to investigate causality and the multi-dimensional nature of the stress-disease relationship, including experimental stressors (Oppliger et al 1998), experimental infections (Warne et al 2011;Kindermann et al 2012;Marino et al 2014) and parasite treatment experiments (Goldstein et al 2005;Raouf et al 2006;Pedersen and Greives 2008;Monello et al 2010). However, experimental approaches have numerous logistical and ethical challenges, particularly when working with small populations of free-ranging endangered species.…”
Section: Approaches To Understand the Relationship Between Stress Andmentioning
confidence: 99%
“…Phenotypic value (i.e., effectiveness) of this type of general defense may vary due to both host genotype and environment. For instance, when defense traits are energetically costly, resistance may be related to available resources (e.g., Oppliger et al 1998;Wiehn and Korpimäki 1998;Ilmonen et al 2000;Moret and Schmid-Hempel 2000;Rigby and Jokela 2000).Independent of costs, inbreeding may increase susceptibility if inbreeding hampers integrity of the immune system. Accordingly, some empirical studies have found evidence for inbreeding depression in resistance traits of the host (Potts et al 1994;Coltman et al 1999;Ouborg et al 2000).…”
mentioning
confidence: 99%
“…Phenotypic value (i.e., effectiveness) of this type of general defense may vary due to both host genotype and environment. For instance, when defense traits are energetically costly, resistance may be related to available resources (e.g., Oppliger et al 1998;Wiehn and Korpimäki 1998;Ilmonen et al 2000;Moret and Schmid-Hempel 2000;Rigby and Jokela 2000).…”
mentioning
confidence: 99%